Self-confocal NIR-II fluorescence microscopy for multifunctional in vivo imaging - Jing Zhou; Tianxiang Wu; Runze Chen; Liang Zhu; Hequn Zhang; Yifei Li; Liying Chen; Jun Qian (Journal of Innovative Optical Health Sciences, 2024)
Fluorescence imaging in the second near-infrared window (NIR-II, 900–1880[Formula: see text]nm) with less scattering background in biological tissues has been combined with the confocal microscopic system for achieving deep in vivo imaging with high spatial resolution. However, the traditional NIR-II fluorescence confocal microscope with separate excitation focus and detection pinhole makes it possess low confocal efficiency, as well as difficultly to adjust. Two types of upgraded NIR-II fluorescence confocal microscopes, sharing the same pinhole by excitation and emission focus, leading to higher confocal efficiency, are built in this work. One type is fiber-pinhole-based confocal microscope applicable to CW laser excitation. It is constructed for fluorescence intensity imaging with large depth, high stabilization and low cost, which could replace multiphoton fluorescence microscopy in some applications (e.g., cerebrovascular and hepatocellular imaging). The other type is air-pinhole-based confocal microscope applicable to femtosecond (fs) laser excitation. It can be employed not only for NIR-II fluorescence intensity imaging, but also for multi-channel fluorescence lifetime imaging to recognize different structures with similar fluorescence spectrum. Moreover, it can be facilely combined with multiphoton fluorescence microscopy. A single fs pulsed laser is utilized to achieve up-conversion (visible multiphoton fluorescence) and down-conversion (NIR-II one-photon fluorescence) excitation simultaneously, extending imaging spectral channels, and thus facilitates multi-structure and multi-functional observation.